2020
DOI: 10.3389/fphar.2020.585984
|View full text |Cite
|
Sign up to set email alerts
|

Grape Seed Proanthocyanidin Extract Ameliorates Cardiac Remodelling After Myocardial Infarction Through PI3K/AKT Pathway in Mice

Abstract: Myocardial infarction is one of the most serious fatal diseases in the world, which is due to acute occlusion of coronary arteries. Grape seed proanthocyanidin extract (GSPE) is an active compound extracted from grape seeds that has anti-oxidative, anti-inflammatory and anti-tumor pharmacological effects. Natural products are cheap, easy to obtain, widely used and effective. It has been used to treat numerous diseases, such as cancer, brain injury and diabetes complications. However, there are limited studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 46 publications
0
18
0
Order By: Relevance
“…In addition, GSPE was reported to induce apoptosis in the CaCo2 colorectal cancer cell line via a mechanism associated with the attenuation of the PI3K/PKB pathway ( 21 ). However, Ruan et al ( 32 ) reported that GSPE is associated with decreased Bax expression and increased Bcl-2 expression, thus playing a critical role in the inhibition of H9C2 cell apoptosis after hypoxic culturing via the PI3K/AKT signaling pathway. Further beneficial effects exerted by GSPE include the prevention of bone loss induced by inflammation via a decrease in the phosphorylation and degradation of NF-κB inhibitor and inhibition of apoptosis via a decrease in the activity of caspases-3 and -9 ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, GSPE was reported to induce apoptosis in the CaCo2 colorectal cancer cell line via a mechanism associated with the attenuation of the PI3K/PKB pathway ( 21 ). However, Ruan et al ( 32 ) reported that GSPE is associated with decreased Bax expression and increased Bcl-2 expression, thus playing a critical role in the inhibition of H9C2 cell apoptosis after hypoxic culturing via the PI3K/AKT signaling pathway. Further beneficial effects exerted by GSPE include the prevention of bone loss induced by inflammation via a decrease in the phosphorylation and degradation of NF-κB inhibitor and inhibition of apoptosis via a decrease in the activity of caspases-3 and -9 ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…The bioactive grape compounds additionally improve appearance, health, and protective skin function, by acting locally as an anti-cellulite agent, improving circulation, preventing and reducing skin hyperpigmentation (freckles, age pigment, and melasma), collagen degradation and denaturation, etc. Furthermore, the influence of antioxidant defense at all levels (cell, tissue organs, system of organs) has also been studied concerning peristalsis in the digestive tract [15,16], myocardial infarction [17,18], and reproductive organs [19,20]. In other words, there is no cell, tissue or organ that does not enjoy the beneficial effects of natural nontoxic unique super-cocktails of grape bioactive substances.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are other related genes, including VEGF-B and VEGF-C, VEGF-A plays a dominant role in regulating angiogenesis (Apte et al 2019 ). PI3K/Akt signaling plays an important role in angiogenesis and exerts a protective role in myocardial infarction (Peng et al 2021 ; Ruan et al 2020 ). Bertrand et al .…”
Section: Discussionmentioning
confidence: 99%